Field screening of wheat genotypes against Karnal bunt caused by Neovossia indica (Mitra) Mund. - Shrvan Kumar, Dhanbir Singh and Vivek Kumar Pandey (Electronic Journal of Plant Breeding, 2014)
One hundred fifty genotypes of wheat were screened for Karnal bunt resistance under artificial inoculation condition in field during 2009-10 rabi seasons. Significant variability in the incidence of disease was observed among genotypes where the per cent disease incidence ranged from 0.2-63.1 at grains harvest stage. Out of one hundred fifty genotypes screened, 12 were rated as highly resistant, 6 as resistant, 6 as moderately resistant and rest as moderately susceptible to highly susceptible genotypes against Karnal bunt of wheat.